Estudio de factibilidad para la creación de una empresa importadora y comercializadora de motores eléctricos adaptables en bicicletas como fuente alternativa de locomoción ecológica y transporte en el Distrito Metropolitano de Quito - Álvarez Garcés, Diana Iveth (2015)
The present research project contains an analysis of the mobility in the city of Quito, the growth of the automotive sector in the last ten years and the importance the bicycle as mean of transportation has taken. This research goal is to determinate the feasibility to create an importing and trading company for bicycle electric motors to grant a solution for the mobility problems in the city. For this purpose the next scheme has been developed: Chapter 1. The problem is acknowledged recognizing its causes and effects, the problem is formulated and structured and the general and specific objectives are determined. Chapter 2. The background and evolution of the bicycle use were analyzed, a description of the bicycle motors characteristics is made and the importing process into Ecuador is detailed. Chapter 3. The methodologic approach to develop this research is described, the size of the sample and the data collection is also determined. Chapter 4. On the market research the survey took place and the data tabulation gives the results to prompt the unsatisfied demand and its projection. Also a SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis is made and the strategies of this project are formulated. Chapter 5. The engineering of the project, its size and localization are determined. The process is described and the human talent needed to start the business. Chapter 6. A financial analysis is made to stablish the feasibility and profitability of the project.